ASEAN Power Grid sebagai Infrastruktur Ketahanan Energi Indonesia di Indo-Pasifik: Perspektif Diplomasi Energi dan Implikasinya bagi Literasi Energi - Tri Siska Windarti; Novky Asmoro; Subur Wahono (PendIPA Journal of Science Education, 2026)
This study repositions the ASEAN Power Grid (APG) primarily as regional energy-resilience infrastructure and examines how energy diplomacy can support Indonesia's strategic use of it in the Indo-Pacific, while mapping its implications for science education. An integrative qualitative literature review was employed to synthesise peer-reviewed studies, ASEAN policy documents, international energy reports, and Indonesian electricity planning documents, prioritising evidence published between 2020 and 2026. Thematic synthesis is organised around five energy-resilience dimensions, namely availability, accessibility, affordability, sustainability, and resilience, together with infrastructure, regulatory, financing, institutional, and technological factors. The analysis shows that the APG can improve supply diversification, system flexibility, reserve sharing, renewable energy integration, and the efficiency of regional electricity trade, and that recent milestones such as the Enhanced APG Memorandum of Understanding of October 2025, the APAEC 2026-2030, the second phase of the Lao PDR-Thailand-Malaysia-Singapore Power Integration Project, and Indonesia's plan to export up to 3.4 GW of low-carbon electricity to Singapore mark a shift towards operational multilateral trade. These benefits remain constrained by interconnection capacity, regulatory fragmentation, financing needs, institutional asymmetry, interoperability, and cyber security. The study also maps the scientific basis of interconnection, namely transmission losses, HVDC conversion, system inertia and frequency control, and battery storage, into science learning topics that can strengthen energy literacy.